Dharmais National Cancer Center Indonesia, The role in National Cancer Control Program of Indonesia - -, Sutoto (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45501514/Dharmais-National-Cancer-Center-Indonesia-The-role-in-National-Cancer-Control-Program-of-Indonesia